Too Cute for Words: Cuteness Evokes the Heartwarming Emotion of Kama Muta - Steinnes, Kamilla Knutsen; Blomster, Johanna Katarina; Seibt, Beate; Zickfeld, Janis H.; Fiske, Alan Page (Frontiers in Psychology, 2019)
A configuration of infantile attributes including a large head, large eyes, with a small nose and mouth low on the head comprise the visual baby schema or Kindchenschema that English speakers call “cute.” In contrast to the stimulus gestalt that evokes it, the evoked emotional response to cuteness has been little studied, perhaps because the emotion has no specific name in English, Norwegian, or German. We hypothesize that cuteness typically evokes kama muta, a social-relational emotion that in other contexts is often labeled in English as being moved or touched, heartwarming, nostalgia, patriotic feeling, being touched by the Spirit, the feels, etcetera. What evokes kama muta is sudden intensification of a communal sharing relationship, either communal sharing between the person and another, or communal sharing between observed others. In accord with kama muta theory, we hypothesize that a kama muta response to cuteness results from a sudden feeling of communal sharing with the cute target. In colloquial terms, the perceiver adores the cute kittens and their heart goes out to them. When a person perceives cute targets interacting affectionately - that is, intensifying communal sharing between them - this should strengthen a kama muta response. We experimentally investigated these predictions in two studies (N = 356). Study 1 revealed that videos of cute targets evoked significantly more kama muta than videos of targets that were not particularly cute. Study 2, pre-registered, found that, as hypothesized, when cute targets interacted affectionately they evoked more kama muta and were humanized more than when they were not interacting. We measured the level of kama muta by self-reports of sensations and signs and of feelings labelled heartwarming, being moved, and being touched. Participants' ratings of kama muta were positively correlated with reported cuteness. In addition, as in our previous research on kama muta elicited by other types of stimuli, trait empathic concern predicted kama muta responses and perceived cuteness. The studies thus provide first evidence that cute stimuli evoke the heartwarming emotion of kama muta.